Therapeutic potential of Cell Cycle Kinases in Breast Cancer - Mir, Manzoor (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book highlights the interrelation between cell cycle regulators and breast cancer phenotypes. It reviews the roles of Cyclin-Dependent Kinases (CDK) in driving cell cycle progression, cell cycle checkpoints and dysregulation in breast cancer. It also examines the prognostic significance of CDKs in breast cancer. and CDK inhibitors for the treatment of metastatic breast cancer. Further, the book discusses the role of different G1 cyclins in differentiation, chromosome stability, and transcriptional regulation in breast cancer. Additionally, it examines the role of immunogenic effects of CDK inhibitors, the mechanism of resistance and the current clinical trials in breast cancer treatment. Towards the end, the book explores cell cycle regulation as an attractive target for targeted drug therapy in breast cancer. This book is a comprehensive yet concise resource for oncologists and researchers interested in exploring the therapeutic potential of Cyclin-Dependent Kinases in breast cancer.
Chapter 1 An introduction to breast cancer -- Chapter 2 Current treatment approaches to breast cancer. Chapter 3 Introduction to cell cycle and its regulators -- Chapter 4 Cell cycle and cancer -- Chapter 5 cell cycle dysregulation in breast cancer -- Chapter 6 Molecular Subtypes of breast cancer and CDK dysregulation -- Chapter 7 Breast tumor micro environment and CDks -- Chapter 8 CDK Dysregulation in Breast Cancer: A Bioinformatics Analysis -- Chapter 9 CDK1 Dysregulation in Breast Cancer -- Chapter 10 CDK4/CDK6 dysregulation in estrogen positive receptor breast cancers -- Chapter 11 Therapeutic implications of CDKs in Breast Cancer -- Chapter 12 Novel CDK Inhibitors in Breast Cancer -- Chapter 13 Targeting CDKs with other chemotherapeutic drugs- A combinatorial approach -- Chapter 14 CDKs in cell-cycle progression and therapeutic strategies in Human breast cancer -- Chapter 15 CDk inhibitor for treatment of breast cancer -- Chapter 16 Response of therapy in cell cycle regulatory genes in breast cancer -- Chapter 17 Different cyclins and their significance in Breast cancer.
Keywords: Cancer; Cancer -- Treatment; Cancer -- Genetic aspects; Cancers; Cancer Therapy; Cancer Genetics and Genomics